Decreased 25-Hydroxyvitamin D Levels in Patients With Vestibular Neuritis - Wu, Yunqin; Hu, Zhizhou; Cai, Minyan; Fan, Zhenyi; Han, Weiwei; Guan, Qiongfeng; Zhou, Min; Li, Li; Yan, Wang; Lu, Xiaoxiong (Frontiers in Neurology, 2019)
Objective: Vestibular neuritis (VN) is characterized by acute onset of vertigo, nausea and vomiting, without auditory or other neurological symptoms. Although the pathogenesis of VN is not yet clear, many studies have shown that a pro- inflammatory environment can lead to the induction and progression of the disease. Considering the importance of vitamin D in modulating the activation, proliferation and differentiation of inflammatory physiological processes, we hypothesized that decreased serum vitamin D may be associated with the development of VN. In this study, we evaluated serum levels of 25-hydroxyvitamin D [25(OH)D] in patients presenting acutely with VN and healthy controls and investigated the possible correlation of serum 25(OH)D levels with VN. Methods: A total of 59 consecutive patients diagnosed with VN within 7 days of symptom onset and 112 age- and sex-matched healthy controls referred to Hwa Mei Hospital, University of Chinese Academy of Science, between February 2017 and February 2019 were recruited. Demographic and clinical data, such as age, sex, height, weight, living habits, ongoing health problems, and medication history, for all subjects were recorded, and levels of 25(OH)D were measured and compared. Results: Serum levels of 25(OH)D were lower in patients with VN than in controls (19.01±6.53 versus 22.94±6.74 ng/ml, p<0.001). Patients with VN had a higher frequency of vitamin D deficiency (61.0 vs. 34.8%, P = 0.001) than did controls. Regression analyses demonstrated that vitamin D deficiency was associated with VN, with an odds ratio of 4.53 (95% CI = 1.342-15.279, P = 0.015). Conclusion: This prospective study is the first to evaluate serum 25(OH)D levels in patients with VN and found that decreased serum 25(OH)D may be associated with VN occurrence.